Role of Land Use Planning on Urban Development in Akure, Nigeria - Enisan, Gbenga; Aluko, Eniola (Journal of Science, Technology and Innovation Research, 2025)
This study examines the role of land use planning in shaping sustainable urban development in Ijapo residential neighbourhood, Akure, Nigeria. With rapid expansion of cities, strategic land use allocation is critical for managing urban growth. This mixed-methods research technique was used which classified the dominant land utilization categories. Surveys and interviews methods were used to explore community perspectives and planning coordination gaps. Key findings show economic development aim slightly outweighs ecological conservation presently, while community accessibility ranks noticeably secondary. Findings also reveals that, housing affordability was pivotal for embedding inclusive accessibility within conservation-oriented managed expansion rather than unintended sprawl. Proposed policy recommendations center on diversifying single-use neighborhoods into mixed-use, mixed-income densities coordinated to support transit and utilities, avoiding strains. Housing Subsidized affordability strategies should also be clustered in conserved nature areas and transit links, transforming segregated zones into sustainable, accessible, vibrant nodes. Also, Outreach programs and digital engagement platforms should expand public participation channels directly shaping priorities. As regional growth escalates development pressures, there must be a spatial blueprint that must lead sustainably through inclusive coordination reforms.